«Չէ Աստ, Այլ Յարեաւ» - Մանուկեան, Նուրհան Արք. (Տպարան Սրբոյ Յակոբեանց)
Ս. Յարութեան տօնի առիթով խոսուած քարօզ։
Keywords: Practical Theology; Armenian church; Christianity; Doctrinal Theology; Liturgy and Ritual